Persepsi Guru terhadap Peran Kepemimpinan Kepala Sekolah - Yunita Aisyah; Inom Nasution; Budi Budi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The purpose of this research is to find out how big the role of teacher perceptions regarding school principal leadership is. The research that has been carried out by researchers is entitled; "Teachers' Perceptions of the Principal's Leadership Role aims to find out: 1) Teachers' Perceptions of the Principal's Leadership Role at Bina Taruna Medan Private Middle School, and 2) What are the teachers' expectations of the leadership system implemented at Bina Taruna Medan Private Middle School. The research design used by the researcher in completing this research is Qualitative with a Phenomenological approach. All information obtained by the researcher is by means of Observation, Interview, and Documentation Study. The researcher interviewed several teachers who taught compulsory subjects at Bina Taruna Private Junior High School in Medan. The results of the research show that: 1) The principal has a very important role in the learning activities in the Bina Taruna Medan Private Junior High School, 2) The principal works with the teaching teachers to improve the learning system effectively and efficiently, 3) The teachers hope that everything that has been considered good must be improved again in order to create competent graduates. The leadership role of the principal plays a very important role in fostering effective education activities. This must also be combined with the cooperation between the Principal and the teachers at the Bina Taruna Medan Private Junior High School.